Flipping Roles, Shifting Souls: Gender Role Stress, Self-Esteem, And Self-Efficacy Of Parents With Interchanged Roles - Desingaño, Armi Grace; Hilario, Paulito; Talamante, Mary Joyce; Amparo, Mary Jane; Belen, John Christian Paolo; Del Espiritu Santo, Jezreel (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study investigated the impact of gender role stress on self-esteem and self-efficacy among parents (N=590) with interchanged roles in Cavite, Philippines. The significance of this research lies in its exploration of evolving gender roles within the context of a traditionally gendered society. Using structural equation modeling (SEM), the study examined relationships between gender role stress, self-esteem, and self-efficacy. The results revealed that gender role stress generally had a negative impact on self-esteem, particularly for working housewives (β=-0.408, p<0.001), while among househusbands it had a positive impact (β=0.552, p<0.001). Self-efficacy was found to be a significant mediator of the relationship between gender role stress and self-esteem among househusband (β=0.115, p<0.05), but not in working housewives (β=-0.03, p>0.05). The study emphasized the need for societal support mechanisms to mitigate the adverse effects of gender role stress and promote mental well-being in these contexts. This research contributes to the understanding of gender dynamics and their psychological implications in non-traditional family structures.